Women's uptake of non‐invasive DNA testing following a high‐risk screening test for trisomy 21 within a publicly funded healthcare system: findings from a retrospective review. (4th January 2015) - Chan, Yiu Man; Leung, Wing Cheong; Chan, Wan Pang; Leung, Tak Yeung; Cheng, Yvonne Kwun Yue; Sahota, Daljit Singh
Abstract Objective The objective of the study was to evaluate the uptake of non‐invasive cell‐free fetal DNA screening test (NIDT) after a high‐risk screening result for trisomy 21 Methods Association between maternal and pregnancy characteristics on women's test choice was assessed after adjusting for confounding factors in Hong Kong Chinese women who had a high‐risk (term risk ≥1:250) first‐trimester or second‐trimester screening test at three public hospitals. Main outcome measures were rate of declining further testing and obstetric and maternal factors impacting on patient's selection of testing options. Results Compared with the pre‐NIDT period, the availability of NIDT resulted in a 45% (P < 0.001) reduction in the rate of refusal for further testing and a decrease from 92.2% to 66.7% in the use of invasive diagnostic test after a positive screening test. Nulliparous women with a spontaneous [adjusted odds ratio (aOR) = 2.18, 95% confidence interval (CI) 1.63–2.92] or assisted reproduction pregnancy (aOR = 3.95, 95% CI 1.6–9.32) were more likely to choose NIDT. Women with an adjusted risk of '>1:10' (aOR = 7.36, 95% CI 4.22–12.8) and '1:10 to 1:50' (aOR = 1.53, 95% CI 1.01–2.32) were more likely to opt for chorionic villi sampling or amniocentesis. Conclusions NIDT reduced the refusal rate. Uptake of NIDT was highest in pregnancies of nulliparous women. © 2014 John Wiley & Sons, Ltd.